Traffic Infrastructure in the Development of the Croatian Traffic System - Šimulčik, Damir; Jurčević, Marinko (Promet - Traffic&Transportation, 2012)
The absence of a long-term traffic policy and of the policyof financing the constntction and maintenance of traffic infrastructurefacilities, represents a synthesis of numerous unresolvedrelations whose negative effects are felt in the overalleconomic and traffic development and consequently theevaluation of national potentials in the field. Adverse aspectcaused by the lack of a clear and feasible policy of financing thetraffic infrastructure facilities, is also a result of not having definedan adequate traffic policy, programme and strategiccourses of development, nor financing models that would be inaccordance with the market and economy system.This indicates that it is necessary to determine a policy forfinancing the constntction and maintenance of traffic infrastntcture,which has to be based on scientific development,team work, availability of plans and programmes to scientistsand experts, determined methodology based on marketing andeconomic logic in defining the programme and strategic tasksand assignments so as to make them feasible.In the near future, intensive preparations for investments inthe overall traffic sysiem are necessary, especially regarding thetraffic infrastntcture facilities - the pivotal points in the processof evaluating the traffic in our national tenitory. Croatia needsto define clearly its strategy in constructing and maintaining thegeneral traffic infrastructure, appointing at the same time thosewho will carry out the given tasks.